Manning's roughness coefficient for ecological subsurface channel with modules. Issue 3 (2nd July 2020) - Mohammadpour, Reza; Zainalfikry, Muhammad Kashfy; Zakaria, Nor Azazi; Ghani, Aminuddin Ab.; Weng Chan, Ngai
ABSTRACT: The ecological subsurface module is the main part of the environmental system to manage storm water, pollution and runoff in urban areas. The novelty of this research is to consider total porosity ( P t ) and the number of modules ( m t ) for estimation of Manning's roughness in the modular channel. To consider the effect of blocks and backwater at the end of the channel, the experimental test was carried out in two conditions of Gate Fully Open (GFO) and Gate Partially Open (GPO). The results indicate that the hydraulic performance of the modular channel is very similar to vegetated channel and Manning's n in the GFO (0.011–0.068) is lower than those in the GPO conditions (0.025–0.20). The three-single modular is able to reduce flow discharge in the range of 13.68% to 17.44%. A sensitivity analysis indicated that of the Manning roughness was greatly affected by the four studied parameters in the following order, Fr (Froude number) >  S (slope) >  P t  >  m t  > depth ratio( y/B ). Finally, two equations with high accuracy were developed to predict Manning's n in both conditions of GFO and GPO.